A microwave-assisted approach to N-(2-nitrophenyl)benzenesulfonamides that enhanced peroxidase activity in response to excess cadmium. Issue 8 (21st February 2019) - Huang, Zhi-You; Liu, Min; Mao, Yi-Jun; Chen, Yu-De; Wang, Yan-Ping; Liu, Chong
Graphical abstract: Highlights: Microwave-assisted approach to nitrophenyl pyrabactin analogues. Excellent yields (91%–97%) and broad substrate scope. Very suitable to prepareflusulfamide (fungicide) . Enhancing POD activity in response to heavy metal stress. Abstract: A facile and efficient approach to N -(2-nitrophenyl) benzenesulfonamides was developed under microwave irradiation. A series of pyrabactin analogues containing nitrophenyl scaffold was obtained in excellent yields. In addition, the method was pretty suitable to prepare flusulfamide. Significantly, the3ae could enhance POD activity in response to heavy metal stress.